Waist Circumference as an Indicator Abdominal Obesity in Middle Age - Ivan Vasiljević; Jovan Gardašević; Miroslav Kezunović; Danilo Bojanić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
Metabolic syndrome was defined in order to identify people with an increased risk. One of five criteria of metabolic syndrome is also an abdominal (central) obesity. The study included 297 subjects, middle aged from Montenegro, 137 (46.12%) male and 160 (53.88%) of the respondents were female. According to the World Health Organization (WHO) about 2.1 billion people suffer from overweight. Analyzing the results of our research, more than worrying fact is that two-thirds of the studied population in middle age are having problems with over-nutrition and obesity. It is estimated that in the world today, about one billion people are overweight, and about 300 million obese